The relationship between leadership styles and job satisfaction among auditors - Nur Fatin Irma Mohd. Farit, 1993- , author 605228 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Perakaunan) - Universiti Teknologi Malaysia, 2017